2018
DOI: 10.1002/ccd.27485
|View full text |Cite
|
Sign up to set email alerts
|

Transubclavian approach: A competitive access for transcatheter aortic valve implantation as compared to transfemoral

Abstract: Our study suggests that TSc approach may be, not only an alternative route to TF approach for TAVI, but even a competitive one in certain patients with increased risk of femoral injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 43 publications
(76 reference statements)
1
18
0
Order By: Relevance
“…Guidewire (E) and short sheath insertion (F). implantation, major vascular complications, and acute kidney injury requiring dialysis when compared to the TF approach [24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guidewire (E) and short sheath insertion (F). implantation, major vascular complications, and acute kidney injury requiring dialysis when compared to the TF approach [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Amat-Santos also suggested that, despite a higher logistic EuroScore (23.7±1.92 vs . 21.17±3.51; P =0.04) and more prevalent coronary and peripheral artery disease, TAx access was performed with a similar 30-day stroke rate, need for new pacemaker implantation, major vascular complications, and acute kidney injury requiring dialysis when compared to the TF approach [ 24 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller published series have demonstrated similar results. 28,29 Transcarotid Mylotte et al described a large series of transcarotid TAVI, with 96 patients undergoing the procedure in three high-volume TAVI centres in France over 4 years (2009-2013). 30 The patients included in this registry had small-calibre, heavily calcified, tortuous or stenotic iliofemoral anatomy or significant descending aortic pathology.…”
Section: Trans-subclavian/transaxillarymentioning
confidence: 99%
“…As highlighted by the authors (and this is the main message from this work, from my perspective), we need to start wondering which alternatives are preferred by well-informed patients; and this information should include the consequences in all aspects related to the quality of life post-intervention. In this regard, alternative approaches to transapical/transaortic access in poor candidates to transfemoral access should be evaluated; transaxillary approach is a very good option with fewer induced comorbidities for the patient [9], but the investigation from Tokarek et al [6] makes us wonder if we have enough information regarding the perception of the patient with this approach as compared to others. Additionally, more than 80% of the patients with prior sternotomy had undergone coronary artery bypass grafting.…”
mentioning
confidence: 99%